Analgesic hypnotic treatment in a post-stroke patient. Issue 3 (18th January 2021) - Formica, Caterina; Micchia, Katia; Cartella, Emanuele; De Salvo, Simona; Bonanno, Lilla; Corallo, Francesco; Arcadi, Francesca Antonia; Giorgianni, Roberto; Marra, Angela; Bramanti, Placido; Marino, Silvia
ABSTRACT: In recent years, hypnotic suggestions have been used in several clinical conditions. This treatment is often used for anxiety treatment, somatization, and post-traumatic stress disorder. Hypnotic analgesia is one of the most clinically useful phenomena of hypnosis. The article describes the case of a patient who underwent hypnotic treatments for hypersensitivity and chronic pain. Results showed an improvement of pain control and a decrease of pain hypersensibility. In addition, during rehabilitative treatments, the patient reported a high level of compliance with the multidisciplinary team. These findings suggest that hypnosis could be a useful treatment for post-stroke pain management.